All mixed up in the terrain: The geographic knowledge of mamelucos applied by Jesuits in the cartographic production of Paraguayan Backlands (1746-1753) - de Moura, Denise A. S. (2023)
Cartographic images made by Jesuits in the 18th century turned out to be transnational and locally mixed cognitive experiences, as these missionary agents of a global institution were forced to establish a collaborative relationship with the multicultural spaces where they settled and undertook their activities. One of the cartographic genres developed by the missionaries, the Paraquariae Provinciae, combined information and geographical knowledge of the mamelucos, a mestizo social type of Amerindian with white Portuguese settler which has been widely acknowledged but poorly elucidated by the historiography making process. The present paper aims to address these issues by applying concepts and methods of critical cartography in order to compare maps built by the Jesuits.